Tinjauan Hukum Islam Terhadap Jual Beli Motor Bekas: Studi Kasus Adanya Kecacatan Tersembunyi Di Showroom Alseda Mandiri Motor Indramayu - Amiruldin, Rizki; Syahril, Syahril; Rachmiati Sunarya, Fitri (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
Buying and selling is something that is justified by religion, of course by fulfilling Islamic Shari'a standards so that buying and selling becomes halal. One example of buying and selling is buying and selling of used motorbikes, even if the motorbikes being sold are second hand or used status, of course the motorbikes must still be fit to be traded freely without any hidden defects on the motorbike. This study aims to find out whether there are hidden defects, and what are the advantages and disadvantages, then how to review Islamic law regarding hidden defects in the Alseda Mandiri Motor Showroom, Indramayu. By using the data collection method through a qualitative approach based on field research, the results of the data obtained, the Alseda Mandiri Motor Showroom did a little cheating such as hidden defects in selling used motorbikes. Therefore, the system and practice of buying and selling carried out by the Showroom is incorrect and prohibited by syara', because of trading of goods (hidden defects).